Public Disclosure and Private Decisions: Equity Market Execution Quality and Order Routing - Boehmer, Ekkehart; Jennings, Robert; Wei, Li (Review of Financial Studies, 2007)
[In 2001, the Securities and Exchange Commission (SEC) required market centers to publish monthly execution-quality reports in an effort to spur competition for order flow between markets. Using samples of stocks trading on several markets, we investigate whether past execution quality affects order-routing decisions and whether the new disclosure requirements influence this relationship. We find that routing decisions are associated with execution quality; markets reporting low execution costs and fast fills subsequently receive more orders. Moreover, the reports themselves appear to provide information that was 2unavailable previously. Our results are consistent with active competition for order flow that can be influenced by public disclosure.]